Vnetje požiralnika, povzročeno s HSV, pri imunokompetentnem otroku - Tiselj, Mateja (Zdravniški vestnik, 2020)
Herpes simplex oesophagitis is a condition that is rarely seen in immunocompetent patients, especially in childhood. However, it is important to also consider the condition in children with symptoms typical of the upper gastrointestinal tract, and to perform endoscopy to confirm the presence of HSV in the mucosa of the oesophagus. Medical management is only symptomatic while antiviral treatment can be added especially in childhood. We present a case report of herpes simplex oesophagitis in a 9-year-old otherwise healthy boy who was admitted to our department with persistent vomiting and inability of oral food intake. Clinical examination revealed pain in the lower abdomen on palpation and clinical signs of dehydration. In laboratory findings, inflammatory markers were mildly elevated. After some basic examinations, we were not able to explain the child%s condition. The performed oesophagogastroduodenoscopy revealed inflammation. Biopsies of the oesophageal mucosa confirmed HSV type 1. Serology markers showed elevated IgM and normal IgG values while sub - sequent testing did not identify an immune disorder.
Keywords: bruhanje; esophagitis; ezofagitis; herpes simplex; vomiting